Curriculum Development Management in Islamic Boarding Schools: Effective Strategies in Countering Radicalism - Moch Subekhan; Nana Suryapermana (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This research analyzes effective managerial strategies in developing Islamic boarding school curricula to prevent radicalism. This research uses a qualitative method with a case study approach focusing on two Islamic boarding schools in Banten Province: Al-Mizan Cikole and Daar Falah Mandalawangi. Data was collected through interviews, observation, and document analysis with stages of reduction, presentation, and conclusion. The results show that the curriculum implemented is integrative, comprehensive, and independent, fostering positive interactions between students, teachers (ustadz), and religious leaders (kyai) in the Islamic boarding school community. Kyai and their administrators serve as role models, and mosques act as centers of activity where no radical ideology is taught or spread. Curriculum planning and content reflect collective efforts to prevent radicalism, providing significant benefits to the quality of education in Islamic boarding schools. The management program for curriculum development to prevent internal and external radicalism has been implemented and carried out systematically from primary education to higher education. It is recommended that the integrative and comprehensive curriculum approach be maintained and continuously improved. Regular training and workshops for teachers and kyai should improve their anti-radicalism education skills. Collaboration with experts and external institutions must be fostered to enrich the curriculum with diverse perspectives. A continuous monitoring and evaluation mechanism must be established to assess the effectiveness of the curriculum in preventing radicalism and make necessary adjustments.